Goal Setting: Weekly Student Conferencing and the Effect on Work Completion in a Montessori Classroom - Peterson, Courtney (My University, 2018)
As educators, teaching students to set attainable goals and to be responsible for the completion of these goals is a life skill that we need in our education system to help our children become successful leaders in the future. This research study was developed to teach students in an E1 Montessori classroom (first through third grade) in a suburban school how to set attainable goals, to identify if weekly individual conferencing between student and teacher is helpful for students to reach these goals, and, to increase work completion throughout the classroom. The participants of this study met weekly to set attainable goals, to reflect on previously set goals, and to record work completion. Results indicated that the majority of students completed more works during the student conferencing and goal setting.
Research Paper, M.S.E., Montessori, UWRF, 2018.
Keywords: conferencing; work completion; goal setting; Montessori